Impacts of COVID-19 on Myanmar’s agri-food system: Evidence base and policy implications - Researchers of the International Food Policy Research Institute and Michigan State University; Aung, Nilar; Cho, Ame; Oo, Than Zaw; Synt, Nang Lun Kham; Ei Win, Hnin; Win, Khin Zin; Zone, Phoo Pye; Zu, A Myint; Lwin, Wuit Yi; Win, Myat Thida; Aung, Zin Wai; et al. (International Food Policy Research Institute, 2020)
Between April and October 2020, the International Food Policy Research Institute (IFPRI) and Michigan State University (MSU), with support from the United States Agency of International Development (USAID) and the Livelihoods and Food Security Fund (LIFT), have undertaken analyses of secondary data combined with regular telephone surveys of actors at all stages of Myanmar’s agri-food system in order to better understand the impacts of COVID-19 on the system. These analyses show that the volume of agribusiness has slowed considerably in Myanmar since COVID-19 restrictions were put in place. There is lower demand from farmers for agricultural inputs and mechanization services and lower volumes of produce traded, especially exports to neighboring countries whose borders are closed. All actors in the agri-food system are facing liquidity constraints and experiencing increased difficulties in both borrowing and recovering loans.